Inclusion of CFRP-Epoxy Composite for End Anchorage in NSM-Epoxy Strengthened Beams - Md. Akter Hosen; Mohd Zamin Jumaat; A. B. M. Saiful Islam (Advances in Materials Science and Engineering)
Nowadays, the use of near surface mounted (NSM) technique strengthening reinforced concrete (RC) structural members is going very popular. The failure modes of NSM strengthened reinforced concrete (RC) beams have been shown to be largely due to premature failure such as concrete cover separation. In this study, CFRP U-wrap end anchorage with CFRP fabrics was used to eliminate the concrete cover separation failure. A total of eight RC rectangular beam specimens of 125 mm width, 250 mm depth, and 2300 mm length were tested. One specimen was kept unstrengthened as a reference; three specimens were strengthened with NSM steel bars and the remaining four specimens were strengthened with NSM steel bars together with the U-wrap end anchorage. The experimental results showed that wrapped strengthened beams had higher flexural strength and superior ductility performance. The results also show that these beams had less deflection, strain, crack width, and spacing.